Peran Strategis Kepemimpinan Wanita dan Kolaborasi Dalam Inovasi UMKM di Kota Surabaya: Pendekatan SWOT Analisis - Titis Tatasari; Dodit Cahyo Nugroho (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2025)
This study analyzes the role of women's leadership and collaboration in driving innovation among MSMEs in Surabaya using a SWOT approach and the Quantitative Strategic Planning Matrix (QSPM). The results indicate that women-led MSMEs have advantages in creativity, perseverance, and adaptability to market dynamics. However, significant internal weaknesses remain, particularly limited production capacity, low digital marketing, and uneven distribution of halal certification and distribution permits. Through the SWOT analysis, the primary strategy that should be prioritized is the WO (Certification & Digitalization) strategy, with the highest score of 5.69. This strategy emphasizes addressing internal weaknesses through product certification, strengthening production capacity, and utilizing digital marketing. Other supporting strategies include ST (Diversification of Raw Materials & Product Innovation) to address the threat of fluctuating raw material prices and changing consumer preferences, and SO (Branding of Typical Surabaya Cakes) to strengthen the identity of local products. Collaboration between MSMEs through cooperatives is also a defensive strategy that can improve the efficiency of raw material and distribution costs. By implementing these strategies, women-owned MSMEs in Surabaya have the potential not only to survive but also to increase their competitiveness through continuous innovation, guaranteed certification, and expanded digital marketing.